Aspectos morfofisiológicos da termotolerância de bromélias - Cleber Juliano Neves Chaves (2013)
Ongoing climate changes will have irreversible impacts on the environment and may have a beneficial effect on the expansion of habitats and productivity of CAM plants. However, little is known about thermotolerance of species with this type of metabolism. This study aimed to understand various aspects that influence the photosynthetic thermotolerance of CAM bromeliads. In the first chapter, we compared the thermotolerance of CAM and C3 bromeliads at more or less light exposed habitats, during distinct seasons. Despite the fact that the highest thermotolerance has been recorded in shaded individuals of Aechmea nudicaulis, a CAM species, the thermotolerance of the exposed ones was similar to the observed at C3 bromeliads, Vriesea bituminosa and V. minarum. Our results suggest that, at the studied site, CAMbromeliads are not more thermotolerant than C3 bromeliads. Seasonal variations of thermotolerance were observed only for the C3 species that occur exclusively at shaded habitat, Vriesea bituminosa. Moreover, great differences were observed in daily thermotolerance values of exposed individuals of A. nudicaulis, which seems to be due to variations in temperature during the day. Nevertheless, no strong relationships werefound between the thermotolerance and other physiological variables. Therefore, CAM metabolism itself does not seem to be responsible for increasing thermotolerance of the CAM plants, and different rates of sun exposure may possibly result in variations of bromeliads hermotolerance. In the second chapter, we also investigated the variations of thermotolerance in different regions and different orientations of the leaves of the cultivated CAM bromeliad, Aechmea blanchetiana. The highest rates of thermotolerance were detectedin the basal portion of the leaves. These results, along with the differences observed for other variables between leaf regions, corroborate the proposal of a functional partition along the leaves of tank bromeliads. The existence of a strategy against heat damage onthe meristem located at the base of the leaves is also hypothesized. A high daily variation of thermotolerance was recorded for A. blanchetiana, with the highest values occurring in the afternoon. Based on the results obtained herein, it was proposed that the thermotolerance is influenced by the accumulation of organic acids and, indirectly, by others variables that affect titrable acidity. The third chapter aimed to investigate, through controlled experiments, the acclimation of leaf fractions of A. blanchetiana kept at different temperatures and to 4 verify its influence on the organic acids accumulation and on the high- and lowtemperature hermotolerance. Leaf samples exhibited a rapid acclimation ofthermotolerance and titrable acidity in reaction to temperature variation. Significant relationships were detected between acidity and tolerance to heat and cold, as well as between these variables and ambient temperature. Finally, the leaf base was found to be highly thermotolerant to extreme temperatures, while the leaf apex presents a highacclimation to non-extreme temperature variations (10-35°C). These results demonstrate the complexity of thermotolerance in CAM bromeliads and open new perspectives for studies to clarify this mechanism.